A taxonomic study on the Bornean and Philippines Sword-tailed Crickets in the genus Rhicnogryllus Chopard, 1925 (Orthoptera: Trgonidiidae; Trigonidiinae) - Tan, Ming Kai; Baroga-Barbecho, Jessica B.; Japir, Razy; Chung, Arthur Y. C.; Wahab, Rodzay Bin Haji Abdul; Yap, Sheryl A. (Zootaxa, 2020)
Rhicnogryllus Chopard, 1925 is a small and relatively unknown group of Sword-tailed Cricket of the subfamily Trigonidiinae. This genus currently comprises 12 species from Asia, Africa (including Madagascar), South America and the Pacific. Species have been recognised by the presence of parallel and elevated veins in both males (which lack stridulatory organs) and females. However, this approach to classifying Trigonidiinae may be outdated and examination of male genitalia can offer better insights into the generic status of these species and how they are related or unrelated. By comparing male genitalia of new materials and old specimens, we describe a new species from the Philippines: Rhicnogryllus? paetensis n. sp., which is similar to the type species. Our hypothesis is that Rhicnogryllus is a non-monophyletic and artificial genus, and that the genus should comprise only Southeast Asian members (since the type species Rhicnogryllus fascipes Chopard, 1925 is known from the Philippines). We are cautiously against describing new genus to avoid adding more confusion until a comprehensive revision to the subfamily and Rhicnogryllus has been undertaken.